Hubungan Strategi Pemasaran Digital dan Inovasi Produk Terhadap Kinerja Bisnis dan Kepuasan Pelanggan Beton Pracetak - Limbong, Beatrik Juliany (Jurnal Adminitrasi Bisnis Nusantara, 2025)
The increasing competition in the precast concrete industry demands companies to develop adaptive and innovative strategies to maintain competitiveness and enhance customer satisfaction. This study aims to analyze the relationship between digital marketing strategy and product innovation on business performance and its implications for customer satisfaction at PT Beton Elemenindo Perkasa. A quantitative approach was applied using a survey method with questionnaires distributed to 100 respondents, including contractors, consultants, and end-users of precast concrete products. Data analysis techniques included data quality tests, path analysis, t-test, F-test, and mediation analysis. The results indicate that digital marketing strategies and product innovation have a positive and significant effect on both business performance and customer satisfaction, directly and through the mediation of business performance. These findings suggest that companies that optimize digital marketing and continuously innovate their products are more likely to improve their performance and strengthen customer loyalty. This research provides a theoretical contribution to the development of technology-based business strategies in the construction industry and practical implications for companies formulating adaptive marketing policies in the digital era.